The work of the people of Medina and its khabar alahad (Journal of Human Sciences, 2025)
Praise be to God, and may God's prayers and peace be upon the Messenger of God, his family, his companions, and those who follow him. The topic of this research is summarized in studying the relationship between the actions of the people of Medina and the hadith reports, as the actions of the people of Medina are considered one of the legislative principles that distinguish the Maliki school. The research includes a study of the important topics of this principle, namely its concept, levels, and its authority, then a statement of the relationship between it and the hadith reports. The method followed in this research is the analytical inductive method. The research is divided into four sections: the first: the concept of the actions of the people of Medina; the second: the levels of the actions of the people of Medina; the third: the authority of the actions of the people of Medina; and the fourth: the relationship between the actions of the people of Medina and the hadith reports. And God is the Grantor of success.